How to Achieve Growth- and Equity-friendly Fiscal Consolidation? A Proposed Methodology for Instrument Choice with an Illustrative Application to OECD Countries - Cournède, Boris (OECD Publishing, 2013)
Despite sustained efforts made in recent years to rein in budget deficits, a majority of OECD countries still face substantial fiscal consolidation needs. The choices made about which spending areas to curtail and which taxes to hike will have implications for near-term activity and long-term growth as well as for equity and the current account. This paper proposes a method for choosing the instruments of consolidation so that they contribute to -- or minimise trade-offs with -- the goals of promoting near-term activity, longterm growth, equity, and global rebalancing. The proposed method is illustrated with detailed simulations for 31 OECD countries which are accompanied by an extensive range of alternative scenarios to confirm the robustness of the findings. The simulations highlight that half of OECD countries can reduce excess debt mainly through moderate adjustments to instruments (such as subsidies, pensions or property taxes) that have at most limited side-effects on other policy objectives. They also show that a smaller number of countries face more difficult choices, having to either make bigger adjustments in areas where spending cuts or tax hikes are least harmful or to rely significantly on consolidation instruments with substantial adverse side-effects. These trade-offs can to a large extent be alleviated through structural reforms in the delivery of public services and in taxation
Keywords: Economics